Are sex and gender dimensions accounted for in NICE guidelines? A systematic review of 223 clinical guidelines - Kate Womersley; Robyn Norton; Marina Politis; Alice Witt; Rachel Hulme; Owen Wilkinson; Ella Haythornthwaite; Veronia Benjamin; Hemali Matharu (BMJ Public Health, 2025)
Introduction The importance of sex and gender in the diagnosis and management of health conditions is well established, but the extent to which sex and gender disaggregated evidence is integrated into UK clinical practice guidelines remains unknown. Recent reviews of clinical guidelines in Canada and Europe identified that limited and inconsistent attention was paid to sex and gender dimensions of health and illness. This study aimed to determine how the UK’s National Institute of Clinical Excellence (NICE) clinical guidelines account for sex and gender.Methods The study reviewed all NICE guidelines categorised as ‘clinical guidelines’ by NICE (223), excluding those solely linked to single-sex conditions (26). Reviewers evaluated whether they included information on sex and/or gender dimensions of disease risk, presentation, investigations and management. They also examined if sex and/or gender dimensions were considered outside of pregnancy, and how the gender of guideline committee chairs and members corresponded to how well sex and/or gender were accounted for.Results Of 197 guidelines reviewed, 120 (61%) referenced sex and/or gender dimensions, with 81 (41%) referencing these dimensions outside of pregnancy and childbearing. A minority of guidelines mentioned sex and/or gender dimensions related to disease pathophysiology (2%), clinical presentation (9%), investigations (15%) and epidemiology (19%). 162 guidelines published details of their committee chairs, and 126 (76%) were men. Committees chaired by women tended to produce guidelines, which scored better for consideration of sex and gender.Conclusion This study highlights key gaps in NICE guidelines which must be addressed through systematic, whole-sector progress to integrate sex and gender disaggregated research into clinical guidelines. As the single focal point responsible for guideline development in England and Wales, NICE has a unique opportunity to establish robust mechanisms to routinely embed this important evidence in guidelines. Multiple initiatives are recommended to identify relevant existing evidence across all clinical specialties.